The quality of pedestrian space in the city: a case study of Olsztyn - Cieślak Iwona; Szuniewicz Karol (Bulletin of Geography. Socio-Economic Series, 2015)
The system of pedestrian urban space is the primary source of information on the state of the space. Walking around a city, we are perceptually building in our mind its physiognomic silhouette, which becomes the basis for evaluating the attractiveness of a city. Unfortunately, pedestrian traffic is rarely the subject of careful planning and design. Usually it regulates itself or is a side-effect of building an extensive system of road communication. On the other hand, concepts of shaping this system as a primary one appear more and more often, and pedestrian space is seen as high priority public space.